2012
DOI: 10.5897/ajpp11.860
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of Pakistani pharmacy students knowledge of herbal medicines in Pakistan

Abstract: The objective of study was to evaluate the knowledge of students on herbal medicines in Pakistan. To evaluate knowledge among the students, a questionnaire based study about herbal medicines was designed. Mean age of responding students was 22 years, some of them had used herbal medicines in past and some were still using. Majority of the students were interested in the information related to herbal medicines. The response of students about herbal medicines was good. But they had a little knowledge about their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 7 publications
1
19
0
Order By: Relevance
“…Poor or insufficient knowledge about herbs has been reported among pharmacy students of Abbottabad and Hazara region of Pakistan [37]. In the present study, we also observed that more than half of the students from Lahore, both pharmacy and non-pharmacy, exhibited adequate knowledge about joshanda, mulethi ( Glycyrrhiza glabara ) and garlic ( Allium sativum ) - the highly popular and easily available herbs with frequent consumption in Lahore.…”
Section: Discussionsupporting
confidence: 73%
“…Poor or insufficient knowledge about herbs has been reported among pharmacy students of Abbottabad and Hazara region of Pakistan [37]. In the present study, we also observed that more than half of the students from Lahore, both pharmacy and non-pharmacy, exhibited adequate knowledge about joshanda, mulethi ( Glycyrrhiza glabara ) and garlic ( Allium sativum ) - the highly popular and easily available herbs with frequent consumption in Lahore.…”
Section: Discussionsupporting
confidence: 73%
“…Previous studies also showed similar results with years of experience and knowledge of pharmacists. [ 28 29 ]…”
Section: Discussionmentioning
confidence: 99%
“…Due to the growing use of herbal medicine and other natural products by patients and consumers, pharmacists now need a basic knowledge of these topics for their professional practices [1,2]. To serve this need, several courses on herbal medicine, e.g., general botany, medicinal botany, etc., are set in pharmacy curriculum.…”
Section: Introductionmentioning
confidence: 99%